Implementation of the Teaching at the Right Level Approach to Improve Learning Outcomes of 10th Grade Students on Probability - Erlita Nur Rahmawati; Rini Setianingsih (MATHEdunesa, 2026)
Learning outcomes in mathematics, particularly in probability, are often uneven due to student’s diverse initial abilities and the limited application of differentiated instruction in a classrooms. This study was conducted to address this issue by implementing the Teaching at the Right Level (TaRL) approach, which focuses on tailoring instruction to students’ actual learning levels rather than their grade level. The purpose of this research is to examine how the TaRL approach can improve students’ learning outcomes in the topic of probability. A descriptive quantitative method was employed, involving 29 students in the experimental class and 30 in the control class. Data were collected through classroom observations of student and teacher activities, student response questionnaires, and cognitive assessments via pretests and posttests. The data analysis included N-Gain calculation, Shapiro-Wilk normality test, paired t-test or Wilcoxon test, and independent t-test or Mann-Whitney test. The results showed that TaRL encouraged active student participation according to their level: high-ability students worked more independently, medium-ability students required occasional guidance, and low-ability students engaged more actively in discussions with consistent support. Teachers successfully applied differentiated instruction based on TaRL principles throughout the discovery learning phases, ensuring structured and adaptive teaching practices. Student responses were highly positive, with many expressing greater enjoyment, engagement, and clarity during learning. A significant difference in learning outcomes was found between the experimental and control groups, indicating that the TaRL approach effectively enhances student achievement by aligning instruction with individual learning needs and promoting active participation in the learning process.